2022
DOI: 10.1002/hec.4507
|View full text |Cite
|
Sign up to set email alerts
|

The effect of absolute versus relative temperature on health and the role of social care

Abstract: Global warming as a result of increasing greenhouse gas emissions is associated with a rise in the intensity and the frequency of extreme weather events (Stott, 2016) with harmful effects on human well-being, especially health and longevity. These effects are likely exacerbated by population aging that enlarges the share of the vulnerable population. The design of (costly) policy measures meant to reduce greenhouse gas emissions, and so the potential impact on population health, relies on precise estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…miners, construction workers, farmers) (Gronlund, 2014). Lastly, access to good quality medical care and social support can protect individuals from the consequences of extreme temperatures (Leyva et al, 2017;Masiero et al, 2022). In Europe, social care programmes tend to be targeted to low SES individuals.…”
Section: Socio-demographic and Geographic Differentials In The Risk O...mentioning
confidence: 99%
See 1 more Smart Citation
“…miners, construction workers, farmers) (Gronlund, 2014). Lastly, access to good quality medical care and social support can protect individuals from the consequences of extreme temperatures (Leyva et al, 2017;Masiero et al, 2022). In Europe, social care programmes tend to be targeted to low SES individuals.…”
Section: Socio-demographic and Geographic Differentials In The Risk O...mentioning
confidence: 99%
“…: > 99 th percentile of the local temperature distribution). Here, we rely on temperature percentiles based on the local temperature to better capture the location-specific adaptation to the climate (Masiero et al, 2022), and we use the total number of days in these temperature ranges, as this better captures the cumulative exposure to heat and cold in the previous year. The use of this approach is also supported by a prominent study (Gasparrini et al, 2015) that found a sizable contribution of moderately cold and moderately high temperatures to mortality, which highlights the importance of considering the full spectrum of temperatures, rather than only extreme events.…”
Section: Variablesmentioning
confidence: 99%
“…Health economists have been working on certain aspects of these challenges more than on others, and these different areas of potential contribution have not previously been brought together in one place. Health economics work in this space includes the impacts of extreme weather events (Escobar Carías et al., 2022; Lee & Li, 2021; Ponnusamy, 2022), extreme temperatures (Adélaïde et al., 2022; Cil & Kim, 2022; Masiero et al., 2022; Mullins & White, 2019), air pollution (Giaccherini et al., 2021; Luechinger, 2014; Palma et al., 2022), and vector‐borne diseases (Sanfelice, 2022).…”
Section: Contributions and Challengesmentioning
confidence: 99%
“…We computed the average minimum and maximum temperature of the grid cells falling within each county boundaries and used it to compute: i) the daily average temperature proxied as the mean between minimum and maximum temperatures, and ii) the monthly temperature bins counting the number of days in 7 categories capturing the percentiles of the county temperature distribution, respectively: days below and equal to the 1 st percentile; from the 1 st to the 5 th percentile; from the 5 th to the 10 th percentile ; from the 10 th to the 90 th (comfort zone); from the 90 th to the 95 th percentile; from the 95 th to the 99 th percentile; above the 99th percentile. We considered this approach preferable to computing groups from raw temperatures as it allowed us to capture the county-specific local climatic condition, which have been shown to vary 36 and to better capture the relationship between temperature and mortality 48 . However, we performed further analysis using alternative temperature bins (see Tables A13-A15 in the Supplementary materials).…”
Section: Meteorological Datamentioning
confidence: 99%